The Urgency of Indonesian Islamic Education in the Era of Society 5.0: Scientific Devotion and Transformation of Education Management - Sari Nusantara Putri; Irma Safitri (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2025)
Islamic education in Indonesia faces a persistent structural tension in the era of Society 5.0: the dichotomy between religious and general knowledge domains, and between centralised and decentralised educational governance. This tension has deep colonial roots, yet its consequences are acutely felt in the present limiting the capacity of Islamic educational institutions to produce graduates who are simultaneously religiously grounded, intellectually rigorous, and professionally competitive. This article argues that overcoming this dichotomy is essential for Islamic educational institutions to remain relevant and competitive. Using a descriptive qualitative approach grounded in a systematic review of the literature, this study examines the conceptual and practical dimensions of de-dichotomisation in Islamic education. The findings indicate that reform requires three interrelated strategies: adopting a disruptive mindset that challenges conventional assumptions about the purpose and scope of Islamic education, developing the capacity to reshape or create educational structures rather than merely preserve them, and cultivating self-driving institutional agency that enables change from within rather than waiting for external mandates. At the curriculum level, reform should proceed through an integrative–interconnective scientific approach that bridges religious and secular knowledge into a coherent epistemic framework. At the governance level, modern management principles including planning, organising, leading, and continuous evaluation must be embedded across Islamic educational institutions as a structural condition for quality and sustainability. Society 5.0 presents not only technological demands but a historical opportunity for Islamic education to reposition itself as a driver of human-centred development that is spiritually grounded, intellectually rigorous, and socially responsive.